Coal and health in Australia - Selvey, Linda (2014)
It is worth remembering that perhaps the biggest health impact of mining and burning coal today is the impact on our climate due to the CO2 that will be released from coal combustion. At Copenhagen in December 2009, world leaders agreed on a target of 2°C warming. At current global emissions we are way off that target, and are set for at least 4°C warming by 2100. If we are going to meet the 2°C degree target, then the world can only emit 1000 billion tonnes of CO2 between 2000 and 2050. In the first 13 years of the century, we’ve already burned 40% of that. If we were to mine and then burn Australia’s known coal reserves, on their own, would use up one-twelfth of the remaining global carbon budget. Whether we burn our coal here or sell it to China, it’s all the same to the atmosphere.